Learning through Learning: Experiential Resonance in an Online Management Course - David Starr-Glass (International School for Social and Business Studies, 2013)
Experiential resonance is a pedagogic approach that allows learners to gaina deeper understanding of the subject matter theory by using that theorydirectly in the structure, dynamics, and learning spaces of the course. Learnersinformed about the application of course theory are asked to reflect onits use. In this preliminary study, management principles were embedded inthe learning spaces of two online distance learning management courses. Apost-course survey, although statistically limited because of the sample size,showed strong learner agreement that management theory had been a resonanttheme in the learning experiences and that its uses had been beneficial.